Investigation of the influence of electron avalanche on the crystallinity of backsheet in solar photovoltaic system for sustainable energy - Zhang, Jia-Wei; Song, Chen (Journal of cleaner production, 2018)
Insulating layer of photovoltaic (PV) modules is subject to irradiation-induced ageing that can affect their security, stability and lifetime. Early potential induced degradation phenomena were founded in the insulating Polyethylene Terephthalate (PET) backsheet of photovoltaic module. However, the designed lifetime of PET insulating backsheet is inconsistent with their practical service time. We have found that the corona discharge in the air provides consistent relative degradation behavior, and that crystallinity values can vary based on different electron avalanche duration. Surface charge evacuation phenomena of PET under varied corona discharge time were also tested. An increase tendency between the chemical degradation and the elevated electron irradiation was investigated. The insulating function and crystallinity properties correlated to its degradation factors as electron irradiation and corona discharge time will be discussed in this work. In this paper, the PET samples were polarized under a corona discharge configuration. Moreover, the surface potential induced by surface charge accumulation effect were tested. A DSC measurement was conducted on these samples. As a result, the bell shaped surface charge distribution and three DSC curves were provided. This paper will present the effect of potential induced aging and electron avalanche caused by corona discharge on the crystallinity of backsheet in solar photovoltaic system for sustainable energy.
Gesehen am 31.03.2020